2004
DOI: 10.1007/s10152-004-0174-6
|View full text |Cite|
|
Sign up to set email alerts
|

Erratum to Bacterial diversity in toxic Alexandrium tamarense blooms off the Orkney Isles and the Firth of Forth

Abstract: PSP toxin content were not accompanied by changes of DGGE band patterns. We therefore presume that the bacterial groups identified in this study were not exclusively associated with toxic A. tamarense, but were generally associated with the phytoplankton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…But, many studies (Grossart et al, 2005;Rooney-Varga et al, 2005;Wichels et al, 2004) have confirmed the reproducibility of PCR and DGGE gels. We assumed that a possible amplification bias for or against a certain sequence would be constant and that changes in relative band intensity would reflect actual changes in the relative abundance of a phylotype.…”
Section: Dgge Profiles Indicate That the Bacterial Community Appears mentioning
confidence: 90%
See 1 more Smart Citation
“…But, many studies (Grossart et al, 2005;Rooney-Varga et al, 2005;Wichels et al, 2004) have confirmed the reproducibility of PCR and DGGE gels. We assumed that a possible amplification bias for or against a certain sequence would be constant and that changes in relative band intensity would reflect actual changes in the relative abundance of a phylotype.…”
Section: Dgge Profiles Indicate That the Bacterial Community Appears mentioning
confidence: 90%
“…Filtration was conducted as soon as the samples were taken to the lab and filters were held at À70 8C until analysis. DNA extraction was performed as described in detail by Wichels et al (2004). Filters were washed using DNA extraction buffer (Tris 50 mmol L À1 , EDTA 20 mmol L À1 , NaCl 100 mmol L À1 , CTAB 2%, pH 8.0), and cell lysis was facilitated by adding lysozyme (2 mg mL À1 ) and SDS (10%).…”
Section: Dna Extractionmentioning
confidence: 99%
“…This hypothesis has been investigated by numerous studies, though the results were conflicting [30,31,32,33,34]. Additionally, some of the methods used to measure bacterial metabolites have subsequently been shown to lack specificity, with compounds thought to be STX later being identified as chemical imposters [32,34].…”
Section: Re-evaluation Of the Three Theories Of Stx Evolution In Dmentioning
confidence: 99%
“…There have been reports concerning the bacteria associated with laboratory maintained strains of A. tamarense (Kodama et al, 1996;Shimizu et al, 1996;Gallacher et al, 1997;Kopp et al, 1997;Babinchak et al, 1998;Hold et al, 2001a;Simon et al, 2002;Zheng et al, 2005) and also A. tamarense blooms (Wichels et al, 2004). These investigations mainly focused on the bacteria associated with laboratory cultures of A. tamarense, bacterial production of PSP and their effects on the PSP production of A. tamarense.…”
Section: Introductionmentioning
confidence: 97%